Resetting the table for people and plants: Botanic gardens and research organizations collaborate to address food and agricultural plant blindness - Krishnan, Sarada; Moreau, Tara; Kuehny, Jeff; Novy, Ari; Greene, Stephanie L.; Khoury, Colin K. (Wiley, 2019)
Societal Impact Statement